Healthcare providers' knowledge of, attitudes to and practice of pre‐exposure prophylaxis for HIV infection. Issue 2 (14th July 2015) - Desai, M; Gafos, M; Dolling, D; McCormack, S; Nardone, A; ,
Abstract : Objectives: Pre‐exposure prophylaxis (PrEP) has proven biological efficacy in reducing the risk of sexual acquisition of HIV. Healthcare providers' (HCPs) knowledge of and attitudes to PrEP will be key to successful implementation. In England, PrEP is only available to men who have sex with men (MSM) through the open‐label randomized PROUD pilot study of immediate or deferred use. Methods: In September 2013, a cross‐sectional survey of UK HCPs distributed through sexual health clinics (219) and professional societies' email lists (2599) and at a conference (80) asked about knowledge of, attitudes to and practice of PrEP. Results: Overall, 328 of 2898 (11%) completed the survey, of whom 160 of 328 (49%) were doctors, 51 (16%) sexual health advisers (SHAs), 44 (14%) nurses and 73 (22%) unspecified. Over a quarter (83 of 311; 27%) were involved in PROUD. Most respondents (260 of 326; 80%) rated their knowledge of PrEP as medium or high. Over half of respondents (166 of 307; 54%) thought PrEP should be available outside of a clinical trial. The main barriers to supporting PrEP availability outside a clinical trial were concerns about current evidence (odds ratio [OR] 0.13), lack of UK‐specific guidance (OR 0.35), concerns about adherence (OR 0.38) and risk of sexual or physical coercion for patients to have condomless or higher risk sex (OR 0.42 in multivariate regression). Just over half (147 of 277; 53%) had been asked about PrEP by patients in the past year, including almost half of those working in a clinic not involved in the PROUD study (86 of 202; 43%). Conclusions: There is support for PrEP availability outside a clinical trial, but HCPs have residual concerns about its effectiveness and negative consequences, and the absence of UK‐specific implementation guidance.